PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPSq) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VII SMPN 33 PADANG - Rizaldi . (Departemen Matematika, 2022)
Having mathematical communication ability is one of the purposes of mathematical learning. In fact, a 7th-grade student at SMPN 33 Padang is still low. In addition to the lack of interest the learners have in learning. It takes effort to address this problem, one way to apply the cooperative learning type Think Pair Square in the study. The purpose of this study to know and describe the impact of application of this model shows the capability of mathematical communication grade VII SMPN 33 Padang. A pra-experimental of one shot case study. Selection of subject class with a purposive sampling technique by defined class VII.1 as a subject class. The result of the test of the subject's class mathematical communication capability after the application of this model is categorized well. Where the average mathematical communication capability of the subject's class learners is 68,39 and a deviation standard of 15,46. Keywords — Mathematical communication ability, Think Pair Square, One Shot Case Stuudy